Computing and comparative analysis of topological invariants of Y‐junction carbon nanotubes. Issue 5 (20th November 2021) - Nadeem, Muhammad Faisal; Shabbir, Ayesha
Abstract: Recent findings of diverse forms of carbon nanostructures have encouraged research on their applications in several areas. They are used as a structural material in electronic and optical devices, involving transistors, photodetectors, plastic, biological sensors, pharmaceutical and medicine, and drug delivery systems. Since the discovery of Y‐shaped carbon nanotubes (CNTs) junctions, they have drawn interest for future electron devices, for example, three‐terminal transistors, amplifiers, and switches. A topological index is a number that is used to study the physicochemical properties of chemical structures. In this paper, we are providing topological properties of CNT Y‐junctions. The results obtained for different types of Y‐junction graphs appeared with comparisons. According to the best of our knowledge and literature, this is the first report about topological indices on this class of CNT junctions. Abstract : Carbon nanotubes junctions have attained a huge attention since their discovery. Carbon nanotube junctions constitute an auspicious material for usage in the aerospace, and many other electronic instruments. The topological indices are used to predict the physical characteristics of chemical structures. In this paper, first and second Zagreb indices, general Randić index, general sum‐connectivity index, atom bond connectivity index, geometric arithmetic index, first and second Zagreb coindices of four types armchair nanotube junctions are computed and give their comparison.